Mutations in the R2 FV Gene Affect the Ratio between the Two FV Isoforms in Plasma - Castoldi, Elisabetta; Rosing, Jan; Girelli, Domenico; Hoekema, Lico; Lunghi, Barbara; Mingozzi, Federico; Ferraresi, Paolo; Friso, Simonetta; Corrocher, Roberto; Tans, Guido; Bernardi, Francesco (Thrombosis and Haemostasis, 2000)
Molecular genetics and biochemical studies were performed in homozygotes for the R2 allele (4070G) in the factor V gene, most of them affected by coronary artery disease. Novel polymorphisms (G642T, 156Ser; T1328C, 385Met/Thr), among which a functional candidate (A6755G, 2194Asp/Gly) located in the C2 domain of FV, were identified in the R2 gene. In chromatographic studies R2 FV appeared qualitatively identical to normal FV. However, a relative increase of the more thrombogenic and more glycosylated FV isoform (FV1) was observed in plasma of 2194Gly homozygotes (mean FV1/FV2 ratio 0.71, 95% CI 0.66-0.77) as compared to R2-free controls (0.37, 95% CI 0.34-0.40). We conclude that carriership of the R2 FV gene is associated with an imbalance between the two functionally different FV isoforms, and propose that genetically determined differential glycosylation of FV could represent a novel mechanism of thrombotic disease.
Keywords: R2 allele; functional polymorphism; FV isoform; FV assay; CAD